CircRNA circ_0092314 Induces Epithelial-Mesenchymal Transition of Pancreatic Cancer Cells via Elevating the Expression of S100P by Sponging miR-671 - Shen, Qian; Zheng, Gang; Zhou, Yi; Tong, Jin; Xu, Sanpeng; Gao, Hui; Zhang, Xiaofan; Fu, Qiang (Frontiers in Oncology, 2021)
Background Circular RNAs (circRNAs) is a novel class of non-coding RNAs that regulate gene expression during cancer progression. Circ_0092314 is a newly discovered circRNA that was upregulated in pancreatic cancer (PAAD) tissues. However, the detailed functions and underlying mechanisms of circ_0092314 in PAAD cells remain unclear. Methods We first determined the expression of circ_0092314 in PAAD and normal tissues and further investigated the functional roles of circ_0092314 in regulating epithelial-mesenchymal transition (EMT) of PAAD cells. We also assessed the regulatory action of circ_0092314 on the microRNA-671 (miR-671) and its target S100P. Results Circ_0092314 was markedly upregulated in PAAD tissues and cells, and its overexpression was closely correlated with worse prognosis of PAAD patients. Functionally, circ_0092314 promotes proliferation, invasion and EMT in vitro and tumor growth in vivo. Mechanistically, we demonstrated that circ_0092314 directly binds to miR-671 and relieve its suppression of the downstream target S100P, which induces EMT and activates the AKT signaling pathway. The tumor-promoting effects caused by overexpression of circ_0092314 could be revered by re-expression of miR-671 in PAAD cells. Conclusions Overall, our study demonstrates that circ_0092314 exerts critical roles in promoting the EMT features of PAAD cells, and provides insight into how elevated expression of circ_0092314 might influence PAAD progression.